FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN DAN SIKAP PERAWAT TERHADAP MAKP - Ratnasari; Arlies Zenitha Victoria; Reny Yulita Sari (Journal of Nursing Care and Biomolecular, 2023)
The Professional Nursing Care Method (MAKP) is a nursing system consisting of structures, processes and professional values ​​that govern the provision of nursing care including an environment that can support the provision of nursing care. The application of MAKP using the nursing care method has not run optimally so far. The purpose of this study was to determine the factors that influence the knowledge and attitudes of nurses towards MAKP. This study used descriptive research using a cross sectional design. The population in the research conducted were all inpatient nurses at Tugurejo General Hospital with a total of 203 nurses. Sampling in this using purposive sampling technique with a sample size of 50 samples. Inclusion criteria for nurses in the Dahlia and Orchid rooms. Data collection tool for knowledge and attitudes of nurses about MAKP. Bivariate analysis using the chi square test. Multivariate analysis using multiple logistic regression tests. The results of the chi square test showed that the p value < 0.25 for the knowledge variables were Age (p value = 0.041) and Years of Service (p value = 0.2381) meaning that there was a relationship between age and length of work on nurses' knowledge. While the attitude variables are gender (p value = 0.043) and training (p value = 0.000) meaning that there is an influence of gender and training on nurses' attitudes. The final multivariate modeling results of the factor that most influences knowledge is Age (p value = 0.061) with OR Exp (B) 9.545. While attitude is training (p value = 0.999) with OR Exp (B) 0.000. The factor that most influences the knowledge of nurses is age. While the factor that influences attitude is training. Keyword: MAKP, Nurse, Knowledge, and Attitude